2009
DOI: 10.1073/pnas.0811003106
|View full text |Cite
|
Sign up to set email alerts
|

High diversity of fungi in air particulate matter

Abstract: Fungal spores can account for large proportions of air particulate matter, and they may potentially influence the hydrological cycle and climate as nuclei for water droplets and ice crystals in clouds, fog, and precipitation. Moreover, some fungi are major pathogens and allergens. The diversity of airborne fungi is, however, not well-known. By DNA analysis we found pronounced differences in the relative abundance and seasonal cycles of various groups of fungi in coarse and fine particulate matter, with more pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
350
2
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(385 citation statements)
references
References 59 publications
30
350
2
3
Order By: Relevance
“…We utilize LSU sequences and identify more than 1,200 OTUs in 103 genera (Table 2). This trend of uncovering greater species diversity has been seen in other aerial fungal studies across the globe (Ebner et al, 1989;Fernández et al, 1998;Gioulekas et al, 2004;Wu et al, 2004Wu et al, , 2007Fang et al, 2005;Fröhlich-Nowoisky et al, 2009). We predict with longer reads and more refined databases, identification of fungal taxa will become more accurate and resolution will reach the species/ strain level, and an even greater fungal diversity will be realized in the future.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…We utilize LSU sequences and identify more than 1,200 OTUs in 103 genera (Table 2). This trend of uncovering greater species diversity has been seen in other aerial fungal studies across the globe (Ebner et al, 1989;Fernández et al, 1998;Gioulekas et al, 2004;Wu et al, 2004Wu et al, , 2007Fang et al, 2005;Fröhlich-Nowoisky et al, 2009). We predict with longer reads and more refined databases, identification of fungal taxa will become more accurate and resolution will reach the species/ strain level, and an even greater fungal diversity will be realized in the future.…”
Section: Discussionmentioning
confidence: 61%
“…Most of these studies depended on spore morphology and/or culture dependent methods for identification. As a majority of fungi are not readily cultured (Pace, 1997;Rappé and Giovannoni, 2003;Fröhlich-Nowoisky et al, 2009) or easily identified by spores alone (Burge, 1985), these results are expected to be an underestimation of airborne fungal diversity (Wu et al, 2004). Metagenomics, a new field in biology, uses new DNA sequencing technologies (e.g., pyrosequencing) to directly sequence and identify environmental microbes (Riesenfeld et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This pathway involved a substratedependent process that suggested that a common CH 4 production pathway exists in all fungal species employed by the authors. An intriguing observation was made by Watanabe et al (2012), who demonstrated slight increases in CH 4 concentrations in blank vials during incubation, which could be explained by airborne fungi (Frohlich-Nowoisky et al, 2009). …”
Section: Fungimentioning
confidence: 99%
“…As a result, the number of studies which have applied culture-independent techniques to the study of airborne bacteria is still limited. For example, such methods were used to assess the diversity of bacteria associated with small-sized particles during dust events (Polymenakou et al 2008) and to characterise the spatial and temporal variations of bioaerosols in different geographical localities and/or different land uses (Angenent et al 2005;Bowers et al 2009Bowers et al , 2010Bowers et al , 2011Brodie et al 2007;Franzetti et al 2010;Frohlich-Nowoisky et al 2009). However, the potential of culture-independent molecular methods, such as quantitative PCR (qPCR), rRNA gene sequencing and hybridisation (i.e.…”
Section: Introductionmentioning
confidence: 99%